Diagnostics of Cattle Buxtonellosis - S. K. Shibitov (Российский паразитологический журнал)
The purpose of the research is to give an analysis to the methods of diagnostics of cattle buxtonellosis.Materials and methods. Feces sampling conducted at the farms for cattle growing with different keeping conditions (private housing, stall-outdoor keeping, stall keeping) from 2013 to 2018. Feces specimens with the mass of 10 g were selected from the animals of different age from rectum or standard collection of fresh feces in housing accommodation for animals. Collected material was preserved by 2% potassium bichromate. For diagnostic purposes parasitological methods for sedimentation, flotation, native and combined methods recommended for diagnostics endoparasitosis were used. Microscopes МБС-10 and ZEISS Axio Imager 2 was used for microscopic evaluation.Results and discussion. For buxtonellosis diagnostics it is recommended: method of sequential irrigation (washout), formalinethereous method and direct smear method. Particularity of Buxtonella sulcata to cause diarrhea in cattle if 1000 or more cysts is present in 1 g of feces should be taken into account allowing for the results of studies. Quantitative methods should be used for this purpose as follows McMaster's modified method or method of examination feces suspension in 5% solution of formalin specifically developed by author.